The Influence of Motivation, Work Environment, and Organizational Culture on Auditor Performance at the Regional Inspectorate of Palu City - Sindi Fatikawati; Jurana Jurana; Fikry Karim; Annastry Widyakusuma (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
Auditor performance plays a crucial role in supporting accountability and transparency in local government administration. Therefore, understanding the factors influencing auditor performance is crucial, particularly work motivation, work environment, and organizational culture. This study aims to analyze the influence of work motivation, work environment, and organizational culture on auditor performance at the Palu City Regional Inspectorate. The study employed a quantitative approach with an associative research design. The study population comprised all active auditors at the Palu City Regional Inspectorate, and the sampling technique employed was saturated sampling, resulting in 32 auditors as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that work motivation had a negative and significant effect on auditor performance, while work environment and organizational culture had a positive and significant effect on auditor performance. Furthermore, work motivation, work environment, and organizational culture simultaneously had a significant effect on auditor performance. These findings suggest that improving auditor performance can be achieved through strengthening organizational culture, creating a conducive work environment, and evaluating motivational practices implemented within the organization.